Metabolic Effects of Recombinant Human Growth Hormone Replacement Therapy on Juvenile Patients after Craniopharyngioma Resection - Shuying Li; Xi Wang; Yaling Zhao; Min Nie; Wen Ji; Jiangfeng Mao; Xueyan Wu (International Journal of Endocrinology)
Objective: To investigate the effect of short-term recombinant human growth hormone (rhGH) replacement therapy on metabolic parameters in juvenile patients following craniopharyngioma (CP) resection. Methods. This retrospective study included 42 cases of juvenile patients that had undergone CP resection in the Department of Endocrinology at the Peking Union Medical College Hospital, from April 2013 to August 2020. According to whether they received growth hormone replacement therapy, the patients were divided into either the growth hormone replacement therapy (GHRT) group (30 cases) or the control group (12 cases). Changes in body mass index (BMI), BMI z-score, transaminase activity, fasting blood glucose (FBG) levels, blood lipid profile, and high-sensitivity C-reactive protein (hsCRP) levels were evaluated after one year of GHRT treatment. Results. The average age of the GHRT group was 13.00 (8.00–14.00) years old and these patients had undergone a CP operation an average of 2.00 (1.62–3.15) years earlier. Prior to receiving GHRT treatment, they received appropriate doses of adrenocortical hormone and thyroid hormone replacement therapy. After one year of GHRT treatment, the average BMI z-score decreased from 1.60 ± 1.76 to 1.13 ± 1.73 (P=0.005). Alanine aminotransferase (ALT) activity decreased from 26.50 (17.00∼98.00) U/L to 18.00 (13.00∼26.48) U/L (P≤0.001), and similar changes were observed with regard to aspartate aminotransferase (AST) and glutamyl transferase (GGT) activity in the GHRT treatment group. The average total cholesterol (TC) decreased from 4.67 (4.10–6.14) mmol/L to 4.32 ± 0.85 mmol/L (P=0.002), and low-density lipoprotein (LDL) levels decreased from 3.05 ± 0.95 mmol/L to 2.56 ± 0.65 mmol/L (P=0.001) in the GHRT treatment group. The average blood urea nitrogen level decreased from 4.53 ± 1.09 mmol/L to 3.92 ± 0.82 mmol/L (P=0.016) and the average serum creatinine (SCr) level decreased from 55.59 ± 12.54 µmol/L to 51.15 ± 10.51 µmol/L (P=0.005) in the GHRT treatment group. The average hsCRP level decreased from 3.23 (1.79∼4.34) mg/L to 0.92 (0.42∼1.21) mg/L in the GHRT treatment group. In the control group, the average ALT activity increased from 26.58 ± 8.75 U/L to 42.58 ± 24.59 U/L (P=0.039), GGT activity increased from 19.0 (13.25–29.25) U/L to 25.00 (14.75–34.75) U/L (P=0.026), and LDL levels increased from 2.27 ± 0.76 mmol/L to 3.43 ± 1.28 mmol/L (P=0.04). Conclusion. GHRT treatment improves the metabolic parameters of juvenile patients that have undergone craniopharyngioma resection by reducing BMI z-scores, low-density lipoprotein, and hsCRP levels and improving liver function.